Contribution of HIV Infection, AIDS, and Antiretroviral Therapy to Exocrine Pathogenesis in Salivary and Lacrimal Glands - Nizamuddin, Imran (Int J Mol Sci, 2018)
The structure and function of exocrine glands are negatively affected by human immunodeficiency virus (HIV) infection and its co-morbidities, including innate and adaptive immune responses. At the same time, exocrine function may also be influenced by pharmacotherapies directed at the infectious agents. Here, we briefly review the role of the salivary glands and lacrimal glands in normal physiology and exocrine pathogenesis within the context of HIV infection and acquired immune deficiency syndrome (AIDS), including the contribution of antiretroviral therapies on both. Subsequently, we discuss the impact of HIV infection and the types of antiretroviral therapy on disease management and therapy development efforts.